2021
DOI: 10.1177/10690727211039957
|View full text |Cite
|
Sign up to set email alerts
|

The Multidimensional Workaholism Scale in a Korean Population: A Cross-Cultural Validation Study

Abstract: This study aimed to provide a reliable and valid measure of workaholism for Korean workers. We translated the Multidimensional Workaholism Scale (MWS) into Korean and validated it with a sample of 1020 full-time Korean employees. An exploratory factor analysis revealed a four-factor solution (Study 1; N = 524), and a confirmatory analysis further demonstrated good model fit of the four-factor structure (Study 2; N = 496). The scale’s concurrent and construct validity was supported by positive correlations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 109 publications
3
22
1
Order By: Relevance
“…Involving a total of 994 participants and two samples, the psychometric properties of the Chinese version of insubordination scale were demonstrated. First, as insubordination was among the first time to be explored in the Chinese context, we conducted an EFA to test the factor structure of this construct following previous validation studies in Study 1 (Kim et al, 2022a; Liu et al, 2019). The results of EFA pointed that insubordination is an unidimensional factor structure with all item loadings greater than .6 threshold (Worthington & Whittaker, 2006), which is similar to the original insubordination scale (Mackey et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Involving a total of 994 participants and two samples, the psychometric properties of the Chinese version of insubordination scale were demonstrated. First, as insubordination was among the first time to be explored in the Chinese context, we conducted an EFA to test the factor structure of this construct following previous validation studies in Study 1 (Kim et al, 2022a; Liu et al, 2019). The results of EFA pointed that insubordination is an unidimensional factor structure with all item loadings greater than .6 threshold (Worthington & Whittaker, 2006), which is similar to the original insubordination scale (Mackey et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Mackey et al (2021) examined the validity test of insubordination scale by testing its negative correlations with task performance and OCBs towards supervisors. To demonstrate the predictive validity of the insubordination scale in the Chinese context, the current study further examined the relationships between insubordination and other related variables used in previous validation studies (Kim et al, 2022a; Meng et al, 2022). We divided these variables into behavioral and attitudinal categories.…”
Section: The Concept and Measure Of Insubordinationmentioning
confidence: 99%
See 1 more Smart Citation
“…In reaction to the shortcomings cited above, the MWS has been developed by Clark et al (2020) Although the four-factor model of the scale has been found the bestfitting model in US and Korean samples (Clark et al, 2020;Kim et al, 2022), the bifactor model (i.e., an overall workaholism factor that lets 16 items load on one factor and the four unrelated factors) has yielded better fit than the purported four-factor model in a Chinese sample (Xu & Li, 2021). Hence, it is necessary to validate the measure's factorial structure in a Dutch context where the work culture is healthier compared to the counties (Fernandez-Crehuet et al, 2016) where the scale has been tested before.…”
Section: The Mws and Its Factorial Structurementioning
confidence: 99%
“…In previous research aiming to validate the MWS, several related constructs have been used to test its convergent validity. In their validation study, Clark et al (2020) have reported that the MWS is expected to be associated with orbiting constructs such as negative affectivity, perfectionist concerns, and job satisfaction, while Kim et al (2022) have reported that the MWS is convergent with perfectionism and work-family conflict in a Korean sample. To expand the previous research finding on the nomological network of the MWS, we examine the convergent validity of the MWS with obsessive passion, workload, and the DUWAS in the Dutch sample.…”
Section: Convergent Validitymentioning
confidence: 99%